2018
DOI: 10.3174/ajnr.a5672
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Borderzone Infarction by CTA in Patients Undergoing Carotid Embolization for Carotid Blowout

Abstract: BACKGROUND AND PURPOSE: Permanent common carotid artery and/or ICA occlusion is an effective treatment for carotid blowout syndrome. Besides postoperative thromboembolic infarction, permanent common carotid artery and/or ICA occlusion may cause borderzone infarction when the collateral flow to the deprived brain territory is inadequate. In this study, we aimed to test the predictive value of CTA for post-permanent common carotid artery and/or ICA occlusion borderzone infarction in patients with carotid blowout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…6 Evaluation of the COW could predict the collateral condition of the patient undergoing carotid embolization. 7 Therefore, a covered stent should be reserved for a bridging procedure indicated for patients with a poor COW or intolerance to an occlusion test. 8 In our patient, the COW integrity was robust; therefore, we selected deconstructive embolization as the treatment procedure.…”
Section: Discussionmentioning
confidence: 99%
“…6 Evaluation of the COW could predict the collateral condition of the patient undergoing carotid embolization. 7 Therefore, a covered stent should be reserved for a bridging procedure indicated for patients with a poor COW or intolerance to an occlusion test. 8 In our patient, the COW integrity was robust; therefore, we selected deconstructive embolization as the treatment procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty‐eight observational studies met all inclusion criteria and were included in the systematic review. There were 18 studies on PAO, 1,4–20 7 studies on stenting 21–27 and 3 studies 28–30 that reported both interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Among our vascular inflammation. Otherwise, CTA can also be used to predict border zone infarction after permanent common carotid artery and/or ICA occlusion by measuring the collateral vessels of the circle of Willis [7]. However, DSA was essential to clarify the sites of pseudoaneurysm, degree of vascular damage, and especially their treatment.…”
Section: Discussionmentioning
confidence: 99%